Persistent Pulmonary Hypertension of Newborn: Analysis of 494 cases in a Tertiary Care Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Persistent pulmonary hypertension (PPHN) or persistent fetal circulation (PFC) is a commonly encountered problem in neonatal and pediatric cardiac intensive care units and cause significant mortality and morbidity.Aim/Objective : To show the outcome of patient of PPHN treated by a cheap, locally available NNF protocol.Methods: It was a retrospective study conducted in pediatric cardiology department of a tertiary care hospital in Dhaka, Bangladesh from February 2014 to March 2019. After diagnosis in noninvasive cardiac laboratory (NIC Lab), all cases were admitted in neonatal and pediatric cardiac intensive care units for specific management using NNF protocol. After 72 hours, echocardiography was repeated, and outcome was analyzed.Results: Out of total 494 cases, 80.56% cases were diagnosed at first week and 4.45% cases were diagnosed at 3rd week of life. Male patients (60.32%) outnumbered female. Babies were delivered by caesarean section in 92.31% cases. PPHN was found alone in 24.69% cases and rest along with other less severe congenital heart diseases. Severe pulmonary hypertension was observed in 63.56% cases. Right ventricular volume was increased in 93.52% cases. Hundred percent neonates were treated with high flow oxygen therapy by optiflow/ nasal cannula/ head box. Antifailure treatment was offered in 73.27% cases, pulmonary vasodilators in 59.51% cases, inotropes in 15.18% cases. Outcome of treatment was analyzed after 72 hours by repeat echocardiography. Four hundred and seventy one (95.34%) cases were cured completely and only 1.01% expired.Conclusion: PPHN is a life threatening condition in neonate only. Early diagnosis and proper management is must for survival. Management by low cost NNF protocol was found effective with 95.34% cure rate and only 1.01% mortality. This protocol may be used for treatment of PPHN in low cost set up.J Bangladesh Coll Phys Surg 2020; 38(4): 176-184